Evaluation Of The Level Of Usefulness Of The “Jeknyong” Application Using The Computer System Usability Questionnare (CSUQ) Method - Yohanna Sitorus; Sarah Astiti; Resad Setyadi (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2023)
The Jeknyong application (Ojeke Inyong) is a household garbage collection service application with a transaction value. However, the use of the Jeknyong application has not been maximized because there are obstacles, such as several features still in development. This study discusses the Evaluation of the Level of Usability of the